Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

implicit differentiation help. Somebody here has got to know how to do this problem... >.<

I got my questions answered at in under 10 minutes. Go to now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly


Get your free account and access expert answers to this and thousands of other questions

Do you know the power rule?
i know how to get y' alone. im having problems putting it in the formular y-y1=m(x-x1)

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

How so?
(2/3) * x^-(1/3) + (2/3) * y^-(1/3) * (dy/dx) = 0 dy/dx = -x^(-1/3) / y^(-1/3)
yes, got that far. now what coolsector?
Fill in y
and x
plug x = -3sqrt(3) , y= 1
i filled in both x and y. and got a number. i used that as my slope in the equation y-y1=m(x-x1)
you get dy/dx = - (3sqrt(3))^(-1/3)
yes, which is -1.732 corect?
mm i ges -0.577 in fact
and x1 = -3sqrt(3) y1 = 1...
dy/dx = -x^(-1/3) / y^(-1/3) i replaced x and y with given points in this, and got -1.732
dy/dx = -(3sqrt(3))^(-1/3) / 1
dy/dx = -(3sqrt(3))^(-1/3) i get -0.577
ok. go on with that then. what is the final answer?
need an equation in y= form
y =1 -0.577(x+3sqrt(3)) y= 1 -0.577x -3 y = -0.577x -2
in fact dy/dx = -1/sqrt(3) so : y = -x/sqrt(3) -2
\[y = \frac{ -x }{ \sqrt{3} } -2\]
says incorrect :/
if we plug x = -3sqrt(3) we get y = 1 right ?
well weird
yeah, i have no idea how to do this problem :/ thanks anyways
im sure it is correct
just tried putting in again, says wrong. :|
going to close post and make another one.

Not the answer you are looking for?

Search for more explanations.

Ask your own question